HUBUNGAN ANTARA KOMUNIKASI DAN PENGAMBILAN KEPUTUSAN DENGAN KINERJA KEPALA SEKOLAH DASAR NEGERI DI WILAYAH JAKARTA TIMUR - Resmin Sihotang (Jurnal Manajemen Pendidikan, 2012)
The objective of the research is to obtain the relationship between communication with the headmasters’ performance, decision making with the headmasters’ performance, communication and decision making with the headmasters’ performance in subdistrict Kramat Jati East Jakarta. The research method used is survey method with correlation and regression approach. The respondents were elementary headmasters’ who are at subdistrict Kramat Jati East Jakarta as many as 75 samples selected by simple random sampling technique. The finding of the research are: (1) there is a positive relationship between communication with performance; (2) there is a positive relationship between decision making with performance; and (3) there is a positive relationship between communication and decision making with performance.Based on these findings, it could be concluded that any changing or variation occured at headmasters’ performance might have been associate with communication and decision making. To minimaze the variation which occurred in headmasters’ performance, these factors such as communication and decision making are necessary to be taken into account.